Acoustic characterization of Thiel liver for magnetic resonance-guided focused ultrasound treatment. Issue 2 (4th March 2017) - Karakitsios, Ioannis; Joy, Joyce; Mihcin, Senay; Melzer, Andreas
Abstract: Background: The purpose of this work was to measure the essential acoustic parameters, i.e., acoustic impedance, reflection coefficient, attenuation coefficient, of Thiel embalmed human and animal liver. The Thiel embalmed tissue can be a promising, pre-clinical model to study liver treatment with Magnetic Resonance-guided Focused Ultrasound (MRgFUS). Material and methods: Using a single-element transducer and the contact pulse-echo method, the acoustic parameters, i.e., acoustic impedance, reflection coefficient and attenuation coefficient of Thiel embalmed human and animal liver were measured. Results: The Thiel embalmed livers had higher impedance, similar reflection and lower attenuation compared to the fresh tissue. Conclusions: Embalming liver with Thiel fluid affects its acoustic properties. During MRgFUS sonication of a Thiel organ, more focused ultrasound (FUS) will be backscattered by the organ, and higher acoustic powers are required to reach coagulation levels (temperatures >56 °C).